Oligarchic initiative in the founding nationalization: the independence and birth of the Central American State - Véliz Catalán, Néstor (2021)
This article begins by establishing methodological details regarding the incorporation of some conceptual and theoretical contributions from the field of Political Science to characterize Central American independence, frequently presented with an epic, heroic halo that distorts historical reality. Next, a set of interpretive criteria generated in a critical reading, typical of the history-science of the independence milestone, is established, which allows defining its oligarchic character. To complement this exposition, we proceed to review how elitist independence conditioned the participation of oligarchic interests in the initial stages of the nationalization process and the configuration of the institutional order.